2019
DOI: 10.29252/jad.2019.1.2.4
|View full text |Cite
|
Sign up to set email alerts
|

A review of amphibian fauna of Sri Lanka: distribution, recent taxonomic changes and conservation

Abstract: The amphibian fauna of Sri Lanka comprises 120 species, including 107 (~90.0%) endemic species. They belong to five families: Bufonidae, Dicroglossidae, Ichthyophiidae, Microhylidae, and Rhacophoridae. Based on distribution, we recognized five zoogeographic zones for them, Central Hills, Dry Zone, Knuckles Range, Lowland Wet Zone, and Rakwana Hills. Fifty three species were reported from the Central Hills (48 endemics [90.6%] and 42 [79.2%] threatened species). 47 species were recorded from the Lowland Wet Zon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 99 publications
1
6
0
Order By: Relevance
“…Three different altitude classes for the distribution of Sri Lankan amphibians were identified, congruent with Batuwita et al (2019): A, 0–800 m a.s.l. ; B, >800–1,700 m a.s.l.…”
Section: Methodssupporting
confidence: 86%
See 2 more Smart Citations
“…Three different altitude classes for the distribution of Sri Lankan amphibians were identified, congruent with Batuwita et al (2019): A, 0–800 m a.s.l. ; B, >800–1,700 m a.s.l.…”
Section: Methodssupporting
confidence: 86%
“…The high‐risk zone (Figure 1) comprises three out of the five amphibian zones of Sri Lanka (Batuwita et al, 2019; MoMD&E, 2019): the Central Highlands, the Knuckles Massif, and the Rakwana Hills. The importance of these regions as local amphibian hotspots is illustrated by the many new species described from them in the recent past (Manamendra‐Arachchi & Pethiyagoda, 2005; Meegaskumbura & Manamendra‐Arachchi, 2005; Meegaskumbura & Manamendra‐Arachchi, 2011; Wickramasinghe et al, 2013b; Senevirathne et al, 2018), as well as the rediscovery of species (Wickramasinghe et al, 2013a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This species was introduced to Madagascar (Frost, 2022). Ongoing taxonomic research in Sri Lanka has revealed that H. tigerinus does not occur in this country, and frogs previously assigned to H. tigerinus are misidentifications of H. crassus (Dutta, 1997;Batuwita et al, 2019). However, the current authors recently collected some specimens from the herpetological survey at Salawin National Park, Mae Hong Son province, northwestern Thailand.…”
Section: Introductionmentioning
confidence: 88%
“…There are several threats to amphibians, even to extinction, such as climate change (Meegaskumbura et al, 2011a), predator attacks, parasite attacks (leach, dragonfly and damselfly larvae, and freshwater crabs), road kills (Karunarathna et al, 2017b), and humanrelated pressure (Batuwita et al, 2019). During the surveys, several threats were recorded that were detrimental to this species.…”
Section: Microhabitatmentioning
confidence: 99%